(untitled) (Journal of Economics and Sustainability, 2021)
Trade openness plays a vital role in boosting the production of the manufacturing sector. Two opposing perspectives identify trade-growth nexus. One posits that trade openness will stifle industrial productivity while the opposing view believes that manufacturing productivity can be enhanced by a trade liberalization regime. This study investigates the instantaneous and jointly dynamic effect of trade openness along with macroeconomic variables (i.e., Malaysian exchange rate and average lending rate) and the event of economic crises on manufacturing sector performance in Malaysia using data from 1981 to 2016. This study employed a distributed lag model. The Augmented Dickey-Fuller (ADF) unit root test was adopted to determine the stationarity of time series data. The empirical results revealed that the effect of both instantaneous and the jointly dynamic effect of the percentage change in trade openness on manufacturing production growth in Malaysia are positive and significant. However, the effects of the percentage change in exchange rate and percentage change in average lending rate are insignificant. Economic crisis has a significant negative impact on Malaysian manufacturing production growth. Therefore, the results strongly recommend that the direction of trade policy in Malaysia should be formulated based on outward-looking strategies. Received 8 March 20. Revised 26 June 20. Accepted 7 Jul 20.